Developing fit-for-purpose funding models for rural settings: Lessons from the evaluation of a step-up/step-down service in regional Australia - Coleman, Mathew; Cuesta-Briand, Beatriz; Ngo, Hanh; Bass, Rachel; Mills-Edward, Naomi; Ennals, Priscilla (Frontiers in Psychiatry, 2023)
Sub-acute mental health community services provide a bridging service between hospital and community care. There is limited understanding of the local factors that influence success, and of the funding implications of delivering services in rural areas. This paper draws from quantitative and qualitative evaluation data from a regional Western Australian service to explore these issues. Consumers satisfaction with the service was high and, overall, admission to the service resulted in positive outcomes. High re-admission rates may be linked to limited community support services following discharge. Our results suggest that outcomes may be enhanced by implementing flexible approaches that address the resource limitations of the rural context, and that the current funding model for sub-acute mental health services in rural Australian may not be fit for purpose. More needs to be understood about how these services can be better integrated with existing support services, and how they can be better funded.